Kebiasaan Baharu (New Normal) Dalam Pelaksanaan Sulh Kes Hadhanah Dan Nafkah Anak: Isu Dan Cabaran: The New Normal of Sulh Implementation in Child Custody (Hadhanah) and Child Support (Nafkah): Issues and Challenges (International Seminar on Syariah and Law (INSLA), 2020)
Islam encourages dispute resolutions through the process of sulh. The implementation of sulh process in the Sharia Courts was introduced to reduce court case backlogs, especially in child custody (hadhanah) and child support (nafkah). With resolutions acheived through sulh process (Majlis Sulh), clients are able to enjoy their new lives because cases are closed in a shorter time with less costs. This article is intended to highlight the new normal of the sulh implementation in child custody (hadhanah) and child support (nafkah) in the midst of the pandemic Covid-19.Past cases were analysed to determine the issues and challenges faced in the implementation of sulh. Qualitative method were used by conducting casual interviews, information gathering from past cases, as well as information from the library and the internet. This research is hoped to beable to contribute to the improvement of the sulh implementation in the Sharia Courts which in turn will bring to more efficient dispute resolutions for child custody (hadhanah) and child support (nafkah). Islam menggalakkan penyelesaian pertikaian secara sulh. Pelaksanaan sulh di Mahkamah Syariah diwujudkan bagi mengurangkan tunggakan kes khususnya hadhanah dan nafkah anak. Penyelesaian yang dicapai melalui Majlis Sulh dapat dinikmati oleh klien dengan menjalani kehidupan baharu kerana kes dapat diselesaikan dalam masa yang singkat dan menjimatkan kos. Artikel ini bertujuan untuk mengetengahkan kepada pembaca bentuk kebiasaan baharu pelaksanaan sulh dalam kes hadhanah dan nafkah anak di Mahkamah Syariah Negeri Sembilan sewaktu berhadapan dengan pandemik covid-19. Analisis terhadap kes-kes terdahulu dilakukan bagi mendapatkan maklumat berkenaan isu dan cabaran yang dihadapi dalam pelaksanaan sulh. Metodologi kajian yang digunapakai adalah melalui pendekatan kualitatif dengan melakukan temubual kasual, pengumpulan maklumat dari failkes-kes terdahulu, perpustakaan dan laman web.Hasil kajian ini dapat menyumbang kepada penambahbaikan perkhidmatan sulh di Mahkamah Syariah yang akan membawa kepada penyelesaian pertikaian hadhanah dan nafkah anak dengan lebih berkesan.